Role of protein and mRNA oxidation in seed dormancy and germination - el-maarouf-bouteau, hayat; meimoun, patrice; Job, Claudette; job, dominique; Bailly, Christophe (Frontiers in Plant Science, 2013)
Reactive oxygen species (ROS) are key players in the regulation of seed germination and dormancy. Although their regulated accumulation is a prerequisite for germination, the cellular basis of their action remains unknown, but very challenging to elucidate due to the lack of specificity of these compounds that can potentially react with all biomolecules. Among these, nucleic acids and proteins are very prone to oxidative damage. RNA is highly sensitive to oxidation because of its single-stranded structure and the absence of a repair system. Oxidation of mRNAs induces their decay through processing bodies or results in the synthesis of aberrant proteins through altered translation. Depending on the oxidized amino acid, ROS damage of proteins can be irreversible (i.e. carbonylation) thus triggering the degradation of the oxidized proteins by the cytosolic 20S proteasome or can be reversed through the action of thioredoxins, peroxiredoxins or glutaredoxins (cysteine oxidation) or by methionine sulfoxide reductase (methionine oxidation). Seed dormancy alleviation in the dry state, referred to as after-ripening, requires both selective mRNA oxidation and protein carbonylation. Similarly, seed imbibition of non-dormant seeds is associated with targeted oxidation of a subset of proteins. Altogether, these specific features testify that such oxidative modifications play important role in commitment of the cellular functioning toward germination completion.